Model-based identification of TNFα-induced IKKβ-mediated and I[kappa]Bα-mediated regulation of NF[kappa]B signal transduction as a tool to quantify the impact of drug-induced liver injury compounds - Oppelt, Angela; Kaschek, Daniel; Huppelschoten, Suzanna; Sison-Young, Rowena; Zhang, Fang; Buck-Wiese, Marie; Herrmann, Franziska; Malkusch, Sebastian; Krüger, Carmen L.; Meub, Mara; Merkt, Benjamin; Zimmermann, Lea; et al. (npj Systems biology and applications, 2018)
Drug-induced liver injury (DILI) is one of the most important obstacles during drug development. More than 1000 drugs have been identified to damage the liver, but the current test systems are poor in predicting DILI. A team of cell biologists, theoretical physicists, and clinical pharmacologists combined experimental data generated in cultured liver cells with mathematical modeling to quantify the impact of the anti-inflammatory drug diclofenac. The analysis demonstrated that diclofenac induces multiple changes in the signal transduction network activated by the tumor necrosis factor alpha (TNFα), one of the known factors to amplify liver toxicity. Data of other liver injury-causing compounds were integrated into the mathematical model and their impact was quantified, thereby demonstrating the potential use of the mathematical model for the further analysis of other compounds in order to improve DILI test systems.
Gesehen am 03.07.2019